2023
DOI: 10.1088/1748-9326/acf1b4
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts and adaptation to permafrost change in High Mountain Asia: a comprehensive review

Prashant Baral,
Simon Allen,
Jakob F Steiner
et al.

Abstract: Changing climatic conditions in High Mountain Asia (HMA), especially regional warming and changing precipitation patterns, have led to notable effects on mountain permafrost. Comprehensive knowledge of mountain permafrost in HMA is mostly limited to the mountains of the Qinghai Tibetan Plateau (QTP), with a strong cluster of research activity related to critical infrastructure providing a basis for related climate adaptation measures. Insights related to the extent and changing characteristics of permafrost in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…The accelerated melting of glaciers leads to increased exposure of moraine soils and eluvium gravels, which can be used as loose solid deposits for agricultural and forestry purposes. However, these loose deposits can also pose a hidden danger as solid material sources of geologic hazards, such as glacier debris ows, landslides, and ice lake outbursts [42]. Therefore, investigating the particle size characteristics of moraine soils in Bengga Valley under global warming is highly signi cant.…”
Section: Site Investigation and Soil Sample Collectionmentioning
confidence: 99%
“…The accelerated melting of glaciers leads to increased exposure of moraine soils and eluvium gravels, which can be used as loose solid deposits for agricultural and forestry purposes. However, these loose deposits can also pose a hidden danger as solid material sources of geologic hazards, such as glacier debris ows, landslides, and ice lake outbursts [42]. Therefore, investigating the particle size characteristics of moraine soils in Bengga Valley under global warming is highly signi cant.…”
Section: Site Investigation and Soil Sample Collectionmentioning
confidence: 99%
“…The degradation of permafrost promotes the upward shift of the alpine timberline. Climate is an important driver of permafrost degradation [7,[54][55][56]. Under the background of global warming, the low-temperature limitation in high latitudes is gradually lifted, while the vegetation shows a certain trend of growth [57].…”
Section: Response Of Alpine Timberlines On Changbai Mountain To Perma...mentioning
confidence: 99%
“…The Tibetan Plateau (TP; Figure 1) hosts the world's most extensive high-altitude permafrost areas, estimated at 1.15 × 10 6 km 2 (2005-2015) . Previous studies showed that permafrost had undergone significant degradation due to anthropogenic warming Baral et al, 2023), as evidenced by increased mean annual ground temperature (MAGT) (Q. , increased active layer thickness (ALT) (Q. Qin et al, 2017), reduced permafrost thickness and areas (D. , and altered geomorphological features (T. Gao et al, 2021;.…”
Section: Introductionmentioning
confidence: 99%